The Analysis of Technical Efficiency of Inbred and Hybrid Lowland Rice Farming Business - Sholikah, Siti; Kadarmanto, Kadarmanto (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 3 (2020): Vol.14, No.3, 2020, 2020)
The background of this research was the unachieved rice productivity of hybrid lowland rice which targeted by the Director General of Crops in 2017. Hybrid lowland rice farmers were assumed did not reach the full efficiency in the use of production factors. This study aimed to explain the general description of inbred and hybrid lowland rice farming business; analyzed the factors that influence the level of business production, and analyzed the technical efficiency and the factors that influence the technical inefficiencies of the farming business. These aims can be answered by the Stochastic Frontier Analysis (SFA) method. The data used was the raw data of the Crops Cost Structure Survey 2017 in East Java Province. This province was chosen because it was the largest production contributor of rice field in Indonesia. Harvesting area, seeds and fertilizers gave a good effect to both for inbred and hybrid lowland rice production, and for hybrid rice production were also supported by labor. The technical efficiency of inbred lowland rice production was higher (81.17 percent) compared to hybrid lowland rice production (70.49 percent). The factors that affected the technical inefficiency of inbred lowland rice were gender, education, pest control, tractors usage, counseling, and the number of labor, while factors that affected to technical inefficiency of hybrid lowland rice, education, pest control, and tractors usage.